Individual and social ramifications of epidemics in the Saudi novels: Safer Berlik and Humma Qifar - Suhail Ahmad; Abdel-Fattah M. Adel; Mashhoor Abdu Al-Moghales; Robert E. Bjork; Mohammed Almahfali (Penerbit Universiti Kebangsaan Malaysia, 2025)
This paper analyzes two Saudi novels within the context of pandemics, employing a cultural imperialism perspective. The novel Humma Qifar قـفـار حـمـى (Fever of Qifar, 2003) is set against the backdrop of the oil boom in Saudi Arabia during the 1950s, while Safer Berlik برلك سفر (Mobilization, 2019) takes place during World War I, in the context of troop mobilization by the Turks and the forced deportation of Arabs to Damascus. These novels document significant moments of cholera and plague epidemics in the 19th century, highlighting the Ottoman Empire's presence in the region. The narratives are intertwined with xenophobic European notions about pandemics. Utilizing concepts of culture and imperialism from Raymond Williams and Herbert Schiller, this study employs cultural materialism as its analytical framework. The analysis seeks to identify commonalities within the historiographies of travelers and resident doctors who emphasized cultural differences between Christians and Muslims, particularly regarding the absence of quarantine measures, predestination, and divine intervention. Through textual, comparative, and thematic analyses, the study highlights themes such as xenophobia, mismanagement of quarantine, and disease transmission through communal gatherings like Haj The paper argues that Humma Qifar recycles the myth of Turkish cruelties, well poisoning, jinn pricking, and divine intervention. Conversely, Safer Berlik encapsulates the portrayal of Turkish soldiers as lustful and tyrannical, reflecting hegemonic European narratives of encroachment on livestock holdings and financial corruption during plague times.